(untitled) (IITM Journal of Business Studies, 2024)
India has a vast population of 1.3 Billion people out of which approximately 44% have a health insurance policy 1. In the FY 2017-18 alone, there were approximately 4.7 million Indians who claimed mediclaim insurance for hospitalization done which included both pre-planned as well as emergency visits to the hospital 2. Each of these claims took around 4-6 hours of processing and follow-up time costing hugely to the claimants 3. The objective of this paper is to evaluate the reduction in Turn Around Time (TAT) and thereby reduce costs in terms of man-hours saved by effective use of Blockchain for the purpose of settling claims. Since Blockchain is a new revolutionary development in the field of online real-time processing of data, there have been very few to Nil studies in this area. Secondary data has been collected from various sources (please check References) and analyzed for effective resolution. The evaluation shows that shifting to a Blockchain based platform for processing medical claims will go a long way in reducing TAT thereby saving both time and cost for the average claimant. Applications: Smart contracts can be applied to automatically indemnify claimants when conditions in the policy are met thereby reducing human intervention in majority of the cases. Conclusion: Blockchain based claim processing platform can ensure that most of the claims are processed on a real time basis.